Stereotactic radiosurgery planning based on time-resolved CTA for arteriovenous malformation: a case report and review of the literature - Turner, Ryan C. (Acta Neurochir (Wien), 2016)
Stereotactic radiosurgery has long been recognized as the optimal form of management for high-grade arteriovenous malformations not amenable to surgical resection. Radiosurgical plans have generally relied upon the integration of stereotactic magnetic resonance angiography (MRA), standard contrast-enhanced magnetic resonance imaging (MRI), or computed tomography angiography (CTA) with biplane digital subtraction angiography (DSA). Current options are disadvantageous in that catheter-based biplane DSA is an invasive test associated with a small risk of complications and perhaps more importantly, the two-dimensional nature of DSA is an inherent limitation in creating radiosurgical contours. The necessity of multiple scans to create DSA contours for radiosurgical planning puts patients at increased risk. Furthermore, the inability to import two-dimensional plans into some radiosurgery programs, such as Cyberknife TPS, limits treatment options for patients. Defining the nidus itself is sometimes difficult in any of the traditional modalities as all draining veins and feeding arteries are included in the images. This sometimes necessitates targeting a larger volume, than strictly necessary, with stereotactic radiosurgery for treatment of the AVM. In this case report, we show the ability to use a less-invasive and three-dimensional form of angiography based on time-lapsed CTA (4D-CTA) rather than traditional DSA for radiosurgical planning. 4D-CTA may allow generation of a series of images, which can show the flow of contrast through the AVM. A review of these series may allow the surgeon to pick and use a volume set that best outlines the nidus with least interference from feeding arteries or draining veins. In addition, 4D-CTA scans can be uploaded into radio-surgery programs and allow three-dimensional targeting. This is the first reported case demonstrating the use of a 4D CTA and an MRI to delineate the AVM nidus for Gamma Knife radiosurgery, with complete obliteration of the nidus over time and subsequent management of associated radiation necrosis with bevacizumab.